1991
DOI: 10.1021/bi00247a016
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics and functional domains of the Fur protein

Abstract: Proteolytic enzymes were used to detect metal-induced conformational changes in the ferric uptake regulation (Fur) protein of Escherichia coli K12. Metal binding results in enhanced cleavage of the N-terminal region of Fur by trypsin and chymotrypsin. Activation of both trypsinolysis sensitivity and DNA binding have similar metal ion specificity and concentration dependencies, suggesting that the conformational change detected is required for operator DNA binding. Isolation and characterization of biochemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
147
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 38 publications
10
147
0
Order By: Relevance
“…In contrast, B. subtilis PerR has been shown recently to detect low levels (Ͻ100 M) of H 2 O 2 by iron-catalyzed oxidation of either of two His residues, His 37 and His 91 (9 (16). However, analysis of E. coli Fur by amino-terminal sequencing and by electrospray ionization MS revealed that the fast migrating band is a proteolytic product of intact protein lacking the amino-terminal nine amino acids (28,29). Recently it has been noted that Zn 2ϩ binding is required for stable folding of the carboxyl-terminal domain of E. coli Fur and for protein dimerization (30).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, B. subtilis PerR has been shown recently to detect low levels (Ͻ100 M) of H 2 O 2 by iron-catalyzed oxidation of either of two His residues, His 37 and His 91 (9 (16). However, analysis of E. coli Fur by amino-terminal sequencing and by electrospray ionization MS revealed that the fast migrating band is a proteolytic product of intact protein lacking the amino-terminal nine amino acids (28,29). Recently it has been noted that Zn 2ϩ binding is required for stable folding of the carboxyl-terminal domain of E. coli Fur and for protein dimerization (30).…”
Section: Discussionmentioning
confidence: 99%
“…7 12). Although there was no helix-turn-helix DNA binding motif found, it has been suggested that ␣-helices in the N-terminal region of E. coli Fur may interact with the major groove of the DNA upon sequence-specific recognition (30,31). However, it is difficult to employ the binding mode of E. coli Fur for the V. anguillarum Fur, since the sequence-specific protein-DNA interactions through the major groove generally require a high conservation of DNA sequence, but the DNA sequences involved in the binding to V. anguillarum Fur show a high diversity without any pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Fur proteins are likely to be dimeric in solution (10,11), and the P. aeruginosa protein was crystallized as a dimer (9). A model for Fur based on the crystal structure of the unbound protein depicts two dimers binding to target DNA.…”
Section: Figmentioning
confidence: 99%
“…Structural analysis of Fur and its DNA binding properties has been most extensively studied in Escherichia coli, Pseudomonas aeruginosa, and Bacillus subtilis, whereas analyses of fur mutants and the identification of genes under Fur control have also been studied in those bacteria and in several other organisms as well. P. aeruginosa Fur was crystallized as a dimer (9), which also appears to be its oligomerization state in solution (10,11). It has been proposed that at least two Fur dimers occupy its target promoter based on the size of protected DNA in footprinting analyses (12).…”
mentioning
confidence: 99%